Estimation of selection response, narrow sense heritability and genetic advance of grain quality characters of F2 and F3 generation in rice (Oryza sativa L.) - Priyanka, A R; Jeyaprakash, P; Robin, S; Raveendran, M (ORYZA-An International Journal of Rice, 2018)
The present investigation was carried out in F2 and F3 generation of rice for estimating the selection response, heritability and genetic advance for grain quality characters. 437 segregants were evaluated in F2 generationfor grain quality characters and forwarded to F3 generation. Based on the phenotypic selection for grain type, 50 single plants were selected in F3 generation for further analysis. The positive significant regression andcorrelation coefficients estimation observed in F2 and F3 generation for kernel length before and after cooking indicated that segregants showed better grain quality and which leads to effective selection. It was found thatthe mean values of kernel breadth, kernel breadth before cooking, kernel breadth after cooking, and linear elongation ratio in F3 generation were higher than F2 generation. Positive value of selection response wascalculated for the parameters viz., kernel breadth, kernel breadth before cooking, and kernel breadth after cooking and linear elongation ratio. In F3 generation highest GA% was calculated for LB ratio, while lowestGA% was calculated for breadth wise expansion ratio which will aid in further selection based on these traits.